Evaluation of healthcare costs and utilization for patients with gout: a population-based matched cohort study. (3rd April 2018) - Lee, Yi-Yun; Tang, Chao-Hsiun; Chen, Jin-Hua; Kuo, Li-Na; Ko, Yu
Abstract: Objectives: To better understand the economic burden of gout patients in Taiwan, a nationwide retrospective study was conducted to compare the healthcare costs and utilization between gout and gout-free patients. Methods: The Longitudinal Health Insurance Database (LHID) 2010 was used to identify gout cases and matched gout-free controls. Gout cases were defined as having (1) at least three instances of diagnoses of gout on medical claims, or (2) one diagnosis of gout with at least one gout-related pharmacy claim in 2011. A control cohort was matched with cases at a 3:1 ratio by age, gender, residential area, and the Charlson Comorbidity Index. All medical utilization and costs per patient within the 365 days following the index date were compared between cases and controls. Results: Out of 993, 332 beneficiaries, a total of 21, 376 matched gout patients met the gout inclusion criteria. Compared to controls, gout patients had more outpatient visits (mean = 31.2 vs 22.6), inpatient visits (mean = 1.7 vs 1.5), and ER visits (mean = 1.9 vs 1.7) (all p  < .0001), as well as more outpatient costs (median = USD $634 vs $404), inpatient costs (median = USD $1330 vs $1254), and ER costs (median = USD $87 vs $89) (all p  < .05). Conclusion: Gout patients had higher medical utilization and costs than gout-free patients. In gout patients, all-cause and gout-related utilization were mostly outpatient visits, whereas most of the all-cause and gout-related costs were due to hospitalization. The study findings could be useful for future economic evaluations and healthcare resource allocation.